2016
DOI: 10.1037/pla0000017
|View full text |Cite
|
Sign up to set email alerts
|

A descriptive study of school counselors’ play therapy experiences with the culturally diverse.

Abstract: This study surveyed 86 Texas school counselors applying play therapy across cultures. Based on the counselors' own comparisons synthesized from play therapy versus talk therapy practices, counselors reported that play therapy facilitated more response from most clients cross-culturally regarding ethnicity (except Asian), gender, and special needs (including schoolchildren in special education and those with disabilities who need accommodations but are unqualified for special education). As an extension of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 21 publications
1
12
0
Order By: Relevance
“…Although studies are beginning to explore the benefits of play for this population, few studies examine the help older adults receive from expressive arts and play therapies. Shen (2016) found that Euro American, African American, Native American, and Hispanic/Latino/Latina children respond better to play therapy than to talk therapy.…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…Although studies are beginning to explore the benefits of play for this population, few studies examine the help older adults receive from expressive arts and play therapies. Shen (2016) found that Euro American, African American, Native American, and Hispanic/Latino/Latina children respond better to play therapy than to talk therapy.…”
Section: Resultsmentioning
confidence: 94%
“…Sexually abused children and adolescents often experience symptoms such as posttraumatic stress symptoms, special needs, anxiety, eating disorders, and depression after abuse incidents occur (Dworkin, Javdani, Verona, & Campbell, 2014; Reyes & Asbrand, 2005; Shen, 2016). Self-mutilation is also common among adolescents who have been, or continue to be, sexually abused (Weierich & Nock, 2008).…”
Section: Therapeutic Approachesmentioning
confidence: 99%
“…For instance, school-based play therapists who practiced in locations with high military populations, history of school violence, and neighborhood gun violence expressed the need to be aware of the impact of including such materials in the school settings for students, parents, and educators. Researchers have also found similar needs for awareness, creativity, and knowledge when including aggressive toys with various populations and settings while understanding the student's history, culture, and ultimate purpose of the aggression (Cheng et al, 2003;Howard, 2021;Kottman, 2011;Shen & Hudspeth, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Numerous research studies have begun to establish play therapy as an intervention with empirical support for a broad range of childhood disorders, including internalizing, externalizing, and developmental problems (Opiola & Bratton, 2018;Reddy et al, 2005Reddy et al, , 2016. Other studies (e.g., Shen, 2016) have investigated the ways in which culture impacts the effectiveness of play therapy and have concluded that it can be successful with children of diverse cultures. However, these studies are not specific to the modalities in this volume, although many of the therapists use at least one or more of these interventions.…”
Section: Play Therapymentioning
confidence: 99%